Testing a Causal Model of Avoidant Insecure Attachment and Marital Conflict Through Self-Differentiation and Cognitive Emotion Regulation: The Moderating Role of Emotional Intelligence in Married Students - Zadehasan , Jamshid; Shahni Yailagh, Manijeh; Shahbazi , Masoud (KMAN Counseling & Psychology Nexus, 2027)
This study aimed to test a causal moderated mediation model explaining marital conflict based on avoidant insecure attachment, with self-differentiation and cognitive emotion regulation as mediators and emotional intelligence as a moderator among married university students. This descriptive-correlational study was conducted using structural equation modeling and conditional process analysis. The statistical population included married undergraduate students at Islamic Azad University, Ahvaz Branch, during the 2025–2026 academic year. A total of 720 married students, including 360 women and 360 men, were selected through multistage random sampling. Data were collected using the Adult Attachment Scale, Marital Conflict Questionnaire, Differentiation of Self Inventory–Short Form, Cognitive Emotion Regulation Questionnaire–Short Form, and Schutte Emotional Intelligence Scale–Revised. Data were analyzed using SPSS, AMOS, and PROCESS Model 14. The results showed that avoidant insecure attachment had a significant positive direct effect on marital conflict in both tested models. Avoidant attachment significantly and negatively predicted self-differentiation and adaptive cognitive emotion regulation, while it significantly and positively predicted maladaptive cognitive emotion regulation. Self-differentiation and emotional intelligence had significant negative direct effects on marital conflict. Adaptive cognitive emotion regulation significantly and negatively predicted marital conflict, whereas maladaptive cognitive emotion regulation significantly and positively predicted marital conflict. The interaction between self-differentiation and emotional intelligence was significant in both models, indicating that emotional intelligence moderated the association between self-differentiation and marital conflict. The interaction between maladaptive cognitive emotion regulation and emotional intelligence was also significant, whereas the interaction involving adaptive strategies was not significant. Conditional indirect effects of avoidant attachment on marital conflict through self-differentiation and maladaptive strategies were significant across different levels of emotional intelligence.